Plastic Waste to Carbon Adsorbent: Activation with Sodium Carbonate and Functionalization with Citric Acid - Ledicia Pereira; María Ángeles Martín-Lara; Guillermo Garcia-Garcia; Concepción Calvo; Tatiana Robledo; Rafael R. Solís; Mónica Calero (Applied Sciences)
Plastic waste management is currently a challenge of great importance. The valorization of non-recyclable fractions into carbonaceous adsorbents is an interesting strategy that promotes the circular economy. In this work, a waste-to-adsorbent strategy was pursued with the char from plastic pyrolysis. The char (non-porous, surface area ~3 m2 g−1) was activated with chemical activation, with sodium carbonate boosting the textural properties (surface area ~418 m2 g−1, pore volume 0.436 cm3 g−1), triggering the formation of activated carbon with a large mesoporosity (71%). X-ray photoelectron spectroscopy and thermal programmed desorption characterization confirmed the enrichment of the surface with carboxylic groups by treatment with citric acid, with a slight loss of textural properties. The activated carbon showed an enhanced adsorption uptake of lead in water (~52 mg g−1 functionalized vs. ~37 mg g−1 non-functionalized) and limited influence on the adsorption of acetaminophen. The preparation costs and the consumption cost per unit of removed pollutants confirm the benefits of the activation and functionalization of the original carbonaceous precursor. However, the possible metal lixiviation from plastic additives and the environmental impact according to a life cycle assessment still make this kind of valorization strategy controversial.